Immunotherapy in Non-Small Cell Lung Cancer: Biological Principles and Future Opportunities - Ilie, M.; Benzaquen, J.; Hofman, V.; Lassalle, S.; Yazbeck, N.; Leroy, S.; Heeke, S.; Bence, C.; Mograbi, B.; Glaichenhaus, N.; Marquette, C.-H.; Hofman, P. (Current Molecular Medicine, 2017)
Immunotherapy aims to amplify the anticancer immune response through reactivation of the lymphocytic response raised against several tumor neo-antigens. To obtain an effective immune response, this therapeutic approach requires that a number of immunological checkpoints be passed, such as the activation of excitatory costimulatory signals or the avoidance of coinhibitory molecules. Among the immune checkpoints, the interaction of the membrane-bound ligand PD-1 and its receptor PD-L1 has received much attention because of remarkable efficacy in numerous clinical trials for various cancer types, including non-small cell lung cancer (NSCLC). However, several limitations exist with these therapeutic agents when used as monotherapy, with objective responses observed in only 30–40% of patients, with the majority of patients demonstrating innate resistance, and approximately 25% of responders later demonstrating disease progression. Recent developments in the understanding of cancer immunology have the potential to identify mechanisms of innate and acquired resistance to immune checkpoint inhibitors through translational research in human samples. This review focuses on the biological basic principles for immunological checkpoint blockade, and highlights the current status and the perspectives of this therapeutic approach in NSCLC patients.
Keywords: immunotherapy